Effect of Pre-Emptive Gabapentin on Anaesthetic and Analgesic Requirements in Patients Undergoing Rhinoplasty (Medical Forum Monthly, 2024)
Objective: to investigate the role of preemptive oral gabapentin (1200mg) to reduce the anesthetic requirement and pos operative analgesia.Study Design: Randomized Control Trial study.Place and Duration of Study: This study was conducted at the Anaesthesia, Intensive Care and Pain Control Department of Nishtar Hospital Multan, Bakhtawar Amin Hospital Multan, CPEIC Hospital Multan and DHQ teaching Hospital Sahiwal from March 2017 to March 2018.Materials and Methods: Hospital ethical board approves the study protocol and gives permission for study. Written consent was obtained from all patients. Patients were divided into two groups (group I and II) by lottery method. Main variables of study were duration of anesthesia, post operative pain, use of ondesteron, nausea vomiting, and Tramadol and diclofenac requirement. SPSS version 24 was used for data analysis.Results: mean total intra‑operative Nalbuphine, time to first analgesic request, total Tramadol consumption in 24 hours and total diclofenac consumption in 24 hours of Group I was 0.98±0.15 mg, 7.57±1.72hours, 81.82±2.41 mg and 52.35±3.16 mg, respectively. While, the mean total intra‑operative Nalbuphine, time to first analgesic request, total Tramadol consumption in 24 hours and total diclofenac consumption in 24 hours of Group II was 2.11±0.38 mg, 2.86±0.51 hours, 139.53±5.15 mg and 90.01±2.53 mg, respectively.Conclusion: Oral gabapentin 1.2g reduce the postoperative analgesic requirement and postoperative pain score to a significant level. Postoperative complications like nausea and vomiting are also low with use of gabapentin.